Point-of-Care Testing (POCT) for Blood Gas and Electrolyte Analysis in Out-of-Hospital Cardiac Arrests’ Management; a Cross-sectional Study - Welawat Tienpratarn; Chaiyaporn Yuksen; Lunlita Chukaew; Chetsadakon Jenpanitpong; Chavin Triganjananun; Suteenun Seesuklom (Archives of Academic Emergency Medicine)
Introduction: Hypokalemia, hyperkalemia, and acidosis are among the reversible causes of out-of-hospital cardiac arrest (OHCA) that can be promptly identified using point-of-care testing (POCT) for blood gas and electrolyte analysis. This study aimed to evaluate the efficacy of POCT in the prehospital setting for OHCA management.